PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA (Studi pada Perusahaan Sub Sektor Batu Bara Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Anisa Anisa; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2017)
This study aims to determine the effect of liquidity (Current Ratio), leverage (Debt to Equity Ratio), profitability (Return on Equity) to the price of shares of mining coal companies listed on the Indonesia Stock Exchange in the period 2013-2016. The dependent variable used is the stock price, while the independent variable is liquidity (Current Ratio), leverage (Debt to Equity Ratio), and profitability (Return on Equity). The population in this study is a coal mining company listed on the Indonesia Stock Exchange as many as 22 companies and then taken as many as 8 companies. The analysis technique used is the classic assumption test, panel data regression analysis with a 5% confidence level, hypothesis testing is performed using the t test and F test. The results of this study indicate that liquidity (Current Ratio) has no significant effect on stock prices, with a probability value of 0.980 is greater than Î± 0.05. leverage (Debt to Equity) has no significant effect on stock prices, with a probability value of 0.386, greater than Î± 0.05. and profitability (Return on Equity) have no significant effect on stock prices with a probability value of 0.343 greater than Î± 0.05. While simultaneous variable liquidity (Current Ratio), leverage (Debt to Equity Ratio), and profitability (Return on Equity) have no significant effect on stock prices with a prob value (F-statistic) of 0.662 greater than Î± 0.05. The coefficient of determination of 0.050 or 5% means the stock price is influenced by liquidity (Current Ratio), leverage (Debt to Equity Ratio), and profitability (Return on Equity) by 5% while the remaining 0.950 or 95% is influenced by other variables outside the research variable.